Optimal segmentation mix of hotel rooms using dynamic programming - Mohamed Nadhar Khan, Sahubar Ali; Abu Bakar, Nur Effa (2011)
Revenue Management refers to the techniques used to allocate limited and perishable resources, such as airplane seats and hotel rooms, to different type of customers in order to maximize the potential revenue within the planning horizon.Pricing strategies and proper segmentation are the core aspects in the successful implementation of revenue management technique. Hotels must decide how many segments to open and the right price that must be charged to the customers in each of these segments in order to optimize their revenue. If they open up too many segments, it will lead to higher fixed cost associated with that segment.On the other hand, the hotels need to open enough number of segments in order to cater to all categories of potential patrons.Thus determining the right mix of the segments to be opened according to the predicted demand level is a crucial element in implementing revenue management strategies.In this paper, we will try to determine the optimal segmentation mix for a hotel chain in Malaysia using dynamic programming method. Currently the hotel chain has seven potential segments and the segments are opened up for the customers without any consideration towards potential cost and revenues.We will try to identify the proper segmentation mix for this hotel in order to optimize its revenue.